CLIMATERIO Y MENOPAUSIA, UNA MIRADA DE GÉNERO - Charlton Lewis, Delfina (2023)
The changing of life is a natural and common process of woman, for than reason we most use mechanism to eradicate the sociocultural myths. The present article is a studies documental of the gender Vision of this experience.